White crane, lend me your wings : a Tibetan tale of love and war - Pemba, Tsewang Y. (New Delhi : Niyogi Books, 2017)
"A posthumous novel by Dr Tsewang Yishey Pemba, the founding father of Tibetan-English literature, White Crane, Lend me your Wings is a historical fiction set in the breathtakingly beautiful Nyarong Valley in the Kham province of Eastern Tibet, in the first half of the twentieth century. Dr Pemba skillfully weaves a dazzling tapestry of individual lives and sweeping events, creating an epic vision of a country and people during a time of tremendous upheaval"
Keywords: Fictional Work; Historical fiction, English China Tibet Autonomous Region